Implications of Metric Choice for Common Applications of Readmission Metrics. (6th June 2013) - Davies, Sheryl; Saynina, Olga; Schultz, Ellen; McDonald, Kathryn M.; Baker, Laurence C.
Abstract : Objective: To quantify the differential impact on hospital performance of three readmission metrics: all‐cause readmission (ACR), 3M Potential Preventable Readmission (PPR), and Centers for Medicare and Medicaid 30‐day readmission (CMS). Data Sources: 2000–2009 California Office of Statewide Health Planning and Development Patient Discharge Data Nonpublic file. Study Design: We calculated 30‐day readmission rates using three metrics, for three disease groups: heart failure (HF), acute myocardial infarction (AMI), and pneumonia. Using each metric, we calculated the absolute change and correlation between performance; the percent of hospitals remaining in extreme deciles and level of agreement; and differences in longitudinal performance. Principal Findings: Average hospital rates for HF patients and the CMS metric were generally higher than for other conditions and metrics. Correlations between the ACR and CMS metrics were highest ( r  = 0.67–0.84). Rates calculated using the PPR and either ACR or CMS metrics were moderately correlated ( r  = 0.50–0.67). Between 47 and 75 percent of hospitals in an extreme decile according to one metric remained when using a different metric. Correlations among metrics were modest when measuring hospital longitudinal change. Conclusions: Different approaches to computing readmissions can produce different hospital rankings and impact pay‐for‐performance. Careful consideration should be placed on readmission metric choice for these applications.